Dampak Media Sosial Terhadap Pendidikan di SD - Nadiva Putri Ananda (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to determine how social media use affects elementary school (SD) curriculum. The study examined how social media affects elementary school students' connections and learning processes using qualitative approaches and case studies in numerous primary schools. The findings demonstrated that social media can both raise students' level of participation in the classroom and help them become aware of focus-detracting factors. In order to successfully control social media use and lessen its negative effects, schools, parents, and students should collaborate, according to the research, which also offers a deeper knowledge of education stakeholders.